WHEN RAIN CLOUDS GATHER- REALIZATION IDENTITY IN BESSIE HEAD’S (International Journal of Food and Nutritional Sciences, 2023)
ABSTARCT: The search for identity is an internal search motivated by a scenario in which a person's true being is called into doubt. Identity shapes self-perception, spatial configuration, and the politics of interpersonal relationships. This dissertation tries to investigate the perceived complex relationship between constructed identity, discrimination, and violence as represented in Bessie Head's work from multiple perspectives, including postcoloniality, materialist feminism, and liminality. Read When Rain Clouds Gather, to understand Bessie Head's ideals on forming and realizing one's identity. The study reveals that Head's vision of identity realization is realized as women play major roles in the success of the agricultural initiative established by Gilbert and Makhaya Maseko. Usually, the bond between Paulina Sobeso and Makhaya the magnanimity of characters like Mma-Millipede are used to convey the ideas of love and fraternity. The female authors are independent-minded, strong-willed women who strive for equality in their marriages. Therefore, this study concludes that Head employs these motifs to support ideas about reconstructing broken lives similar to her own.